Water-based flexographic ink and printed matter
The aqueous flexo ink with acrylic resin emulsion, barium sulfate, and styrene maleic acid resin addresses the issues of drying, washability, and stability, ensuring effective printing on diverse paper substrates.
Patent Information
- Application Number
- JP2023101293
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2025-01-09
AI Technical Summary
Existing water-based flexographic inks lack sufficient drying properties, washability, transferability, and stability over time, particularly when applied to a wide range of paper substrates including water-repellent liner paper.
Aqueous flexo ink formulation containing an acrylic resin emulsion, barium sulfate, and a styrene maleic acid resin, with specific particle sizes and mass ratios, enhancing synergistic effects for improved printing and transferability.
The ink exhibits excellent drying properties, washability, transferability, and stability over time, suitable for a variety of paper substrates including water-repellent liner paper.
Smart Images

Figure 2025001684000001 
Figure 2025001684000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an aqueous flexographic ink. In particular, the present invention relates to an aqueous flexographic ink intended for printing substrates such as cardboard, carton paper, wrapping paper, plastic film, aluminum foil, etc. The present invention also relates to an aqueous flexographic ink that has drying properties, washability, transferability, abrasion resistance, and stability over time in flexographic printing and is suitable for obtaining high-quality printed matter. [Background technology]
[0002] In recent years, in the printing field of packaging containers for daily necessities and industrial materials, there is a demand for printing inks with excellent print density, leveling properties, and high-speed printing properties from the perspective of aesthetics and economy. Among these, water-based inks are used in cardboard and paper container applications as a measure for occupational safety, disaster prevention, and working environment. Among water-based inks, water-based flexographic inks are used in flexographic printing methods, and allow for thinner ink layers and faster printing than gravure printing methods.
[0003] For example, Patent Document 1 discloses an aqueous ink composition consisting of a specific polyethylene oxide and an alkali metal salt, Patent Document 2 discloses a composition consisting of a specific styrene maleic acid monoester, Patent Document 3 discloses a resin composition having a specific alkylene oxide group, Patent Document 4 discloses a composition in which a polyvalent inorganic cation is blended with a specific resin composition, and Patent Document 5 discloses an aqueous printing ink composition using a specific surfactant. However, since these aqueous inks only adjust the surface tension, improvements are required in terms of transferability to paper substrates or stability over time of the ink. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 55-12192 [Patent Document 2] Japanese Patent Application Publication No. 179504 / 1983 [Patent Document 3] Japanese Patent Application Publication No. 54-74104 [Patent Document 4] Japanese Patent Publication No. 63-227674 [Patent Document 5] Japanese Patent Application Publication No. 09-217034 Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention aims to provide a water-based flexographic ink that is excellent in drying properties, washability, transferability, abrasion resistance, and stability over time, and in particular, is applicable to a wide range of paper substrates, including water-repellent liner paper. [Means for solving the problem]
[0006] As a result of extensive research into the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by using the water-based flexographic ink described below, and have thus completed the present invention.
[0007] That is, the present invention relates to a water-based flexographic ink comprising an acrylic resin emulsion, barium sulfate, and a styrene-maleic acid resin.
[0008] The present invention also relates to the above water-based flexographic ink, wherein the average particle size of the barium sulfate is 0.1 to 2 μm.
[0009] The present invention also relates to the above water-based flexo ink, wherein the oil absorption of barium sulfate is 10 to 100 ml / 100 g.
[0010] The present invention also relates to the above water-based flexographic ink, further comprising a color pigment.
[0011] The present invention also relates to the above water-based flexographic ink, wherein the solids mass ratio between the color pigment and barium sulfate is 99:1 to 30:70.
[0012] The present invention also relates to the above water-based flexographic ink, wherein the solid content mass ratio of barium sulfate to styrene-maleic acid resin is 99:1 to 30:70.
[0013] The present invention also relates to the above water-based flexographic ink, wherein the styrene-maleic acid resin has an alkyl ester structure.
[0014] The present invention also relates to the above water-based flexographic ink, which further contains a water-soluble acrylic resin.
[0015] The present invention also relates to a printed matter having a printed layer made of the above-mentioned water-based flexographic ink on a substrate. Effect of the Invention
[0016] The present invention makes it possible to provide a water-based flexographic ink that is excellent in drying properties, washability, transferability, abrasion resistance and stability over time, and can be applied to a wide range of paper substrates, including water-repellent liner papers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The following describes in detail the embodiments of the present invention. However, the following description of the components is merely an example of an embodiment of the present invention, and the present invention is not limited to these contents as long as it does not deviate from the gist of the present invention.
[0018] [Water-based flexographic ink] The present invention relates to a water-based flexographic ink containing an acrylic resin emulsion, barium sulfate, and a styrene-maleic acid resin. In conventional water-based flexographic inks, a large amount of surfactant is added to lower the surface tension to improve transferability, but this method causes a decrease in defoaming ability and a decrease in water resistance of the printed coating. In addition, pinholes are easily generated in the printed layer, and it is difficult to maintain printability and transferability, especially on surface-treated paper substrates. However, the water-based flexographic ink of the present invention is considered to improve printability and transferability to substrates by using styrene-maleic acid resin and barium sulfate at the same time, and to maintain a high level of transferability to a wide range of paper substrates due to a synergistic effect. Here, "wide range of paper substrates" includes paper substrates containing a resin layer and water-repellent paper. In addition, the ink has improved stability over time. Note that this explanation is based on technical considerations only and does not limit the invention in any way. In the present invention, it is preferable that the ink further contains a water-soluble acrylic resin and / or a color pigment.
[0019] <Acrylic resin emulsion> The acrylic resin emulsion used in the aqueous flexographic ink of the present invention refers to an aqueous emulsion resin containing an acrylic resin structure. The acrylic resin emulsion is more preferably a styrene-acrylic resin emulsion, and even more preferably a core-shell type acrylic resin emulsion. The acrylic resin emulsion refers to a form in which the acrylic resin itself is insoluble or poorly soluble in water, but the resin is dispersed in the form of small particles in an aqueous medium and stabilized. The average particle size of the acrylic resin emulsion measured by a dynamic light scattering method is preferably 10 to 500 nm, more preferably 20 to 300 nm, and even more preferably 30 to 200 nm.
[0020] The resin contained in the acrylic resin emulsion preferably has an acid group, and in that case, the acid value is preferably from 20 to 200 mgKOH / g, more preferably from 20 to 150 mgKOH / g, and even more preferably from 20 to 100 mgKOH / g. The weight average molecular weight of the acrylic resin emulsion is preferably 2000 to 600000, more preferably 50000 to 600000, and even more preferably 70000 to 600000. The glass transition temperature of the resin contained in the acrylic resin emulsion is preferably -30 to 100°C, more preferably 0 to 100°C, and even more preferably 30 to 90°C. When it is within the above range, the abrasion resistance and stability over time become good.
[0021] The acid value is the number of milligrams of potassium hydroxide required to neutralize the acidic groups contained in 1 g of resin solid content, and is measured in accordance with JIS K0070.
[0022] The weight average molecular weight (Mw) can be measured, for example, by GPC (gel permeation chromatography), and can be calculated as a molecular weight converted using polyethylene glycol as a standard substance. The measuring device can be a GPC device such as Shodex GPC-401 manufactured by Showa Denko K.K., and the column can be a Shodex OHpak LB-805 manufactured by Showa Denko K.K., and the detector can be an RI (differential refractometer), and the measurement temperature is preferably a column temperature of 20 to 50°C. The eluent can be an aqueous solution of 0.1N NaNO3, and the flow rate is generally 0.2 to 5.0 mL / min.
[0023] The glass transition temperature can be measured, for example, using a differential scanning calorimeter (DSC measuring device, Shimadzu Corporation's "DSC-60A"), and the temperature of the inflection point in the baseline shift can be used as the glass transition temperature. The measurement is preferably performed in a nitrogen atmosphere, with the measurement temperature range being -100 to 200°C and the heating rate being 1 to 5°C / min.
[0024] The resin contained in the acrylic resin emulsion is obtained by polymerizing an acrylic monomer. Suitable examples of the acrylic monomer include acrylic acid esters and methacrylic acid esters. Suitable examples of the acrylic acid esters include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, benzyl acrylate, dimethylaminoethyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, and glycidyl acrylate. Suitable examples of the methacrylic acid esters include methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, dimethylaminoethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and glycidyl methacrylate. Additionally, carboxylic acid-containing monomers such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, and itaconic acid are suitable, and their anhydrides and half esters can also be used. Among the above, the acrylic monomer preferably includes methyl acrylate, ethyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, acrylic acid, methacrylic acid, maleic acid, and itaconic acid. Examples of the styrene monomer constituting the styrene-acrylic resin emulsion include styrene, α-methylstyrene, β-methylstyrene, etc. Among these, it is preferable that the styrene monomer contains α-methylstyrene.
[0025] As the acrylic resin emulsion, a commercially available product can be used, for example, PE-1304, JE-1113, etc. manufactured by Seiko PMC Corporation.
[0026] <Water-soluble acrylic resin> The water-based flexographic ink of the present invention preferably further contains a water-soluble acrylic resin. The water-soluble acrylic resin refers to a resin in which the acrylic resin itself is dissolved in water alone. The water-soluble acrylic resin is preferably a water-soluble styrene acrylic resin. The water-soluble acrylic resin preferably has an acid group, and in this case, the acid value is preferably 150 to 350 mgKOH / g, and more preferably 200 to 300 mgKOH / g. When the water-soluble acrylic resin has an acid group and the acid value is within the above range, the cleaning property and transferability are good. The weight average molecular weight of the water-soluble acrylic resin is preferably 1500 to 50000, more preferably 3000 to 40000, and even more preferably 5000 to 30000. The glass transition temperature of the water-soluble acrylic resin is preferably 40 to 130°C, and more preferably 60 to 100°C. When the weight average molecular weight and glass transition temperature of the water-soluble acrylic resin are within the above ranges, the cleaning property and transferability are good. Metastasis The properties are improved.
[0027] As the water-soluble acrylic resin, commercially available products may be used, for example, GL-2439 and YL-1098 manufactured by Seiko PMC Corporation.
[0028] From the viewpoints of abrasion resistance and washability, the solids ratio of the acrylic resin emulsion to the water-soluble acrylic resin is preferably 90:10 to 30:70, and more preferably 80:20 to 60:40.
[0029] <Styrene maleic acid resin> The styrene-maleic acid copolymer resin preferably has an acid group, and in that case, the acid value is preferably from 50 to 400 mgKOH / g, and more preferably from 100 to 350 mgKOH / g.
[0030] The weight average molecular weight of the styrene-maleic acid copolymer resin is preferably 500 to 100,000, more preferably 1,000 to 50,000, and even more preferably 2,000 to 10,000. When it is within the above range, the transferability is good. The styrene-maleic acid resin preferably has an alkyl ester structure derived from alkyl esterification of carboxylic acid of maleic acid. The degree of alkyl esterification of styrene-maleic acid is preferably 10 to 80 mol%, more preferably 20 to 70 mol%, and even more preferably 40 to 60 mol%. When it is within the above range, the transferability is good. The degree of alkyl esterification refers to the molar ratio of carboxylic acid groups esterified with alkyl groups to all carboxylic acid groups in the styrene-maleic acid resin.
[0031] As the styrene-maleic acid resin, commercially available products may be used, for example, M-30 manufactured by Seiko PMC Corporation, and Alastar series manufactured by Arakawa Chemical Industries, Ltd. may be used.
[0032] <Extender pigment> The water-based flexographic ink of the present invention contains barium sulfate. The water-based flexographic ink of the present invention may contain an extender pigment other than barium sulfate. Examples of extender pigments other than barium sulfate include calcium carbonate, magnesium carbonate, white carbon, talc, aluminum hydroxide, aluminum hydroxide, magnesium hydroxide, alumina white, silica powder, diatomaceous earth, synthetic silica, calcium silicate, attapulgite, sericite, mica, silica, hydrotalcite, bentonite, zeolite, kaolin, pyrophyllite, etc., and the average particle size of the extender pigment measured by electron microscopy is preferably 0.1 to 2 μm, more preferably 0.2 to 1 μm. The oil absorption is preferably 10 to 100 ml / 100 g, more preferably 20 to 70 ml / 100 g.
[0033] From the viewpoint of drying property and transferability, the solid content ratio of barium sulfate to styrene-maleic acid resin in the water-based flexographic ink of the present invention is preferably 99:1 to 30:70, more preferably 99:1 to 50:50, and even more preferably 99:1 to 70:30.
[0034] (Barium Sulfate) Barium sulfate may be synthesized by either method, such as eluted barium sulfate (baryte powder), which is a crushed product of barite mineral, generally called natural barite, or precipitated barium sulfate produced by chemical reaction. Examples of such barium sulfate include barium sulfate A200 and barium sulfate P-30 manufactured by Takehara Chemical Industry Co., Ltd.
[0035] (Calcium Carbonate) Calcium carbonate is classified into heavy calcium carbonate made by crushing and classifying limestone, and light calcium carbonate (synthetic calcium carbonate, precipitated calcium carbonate, PCC) made by precipitating fine crystals in liquid through a chemical reaction, and may be synthesized by either method. Examples of such calcium carbonate include the Sunlight series manufactured by Takehara Chemical Industry Co., Ltd.
[0036] (silica) Examples of silica include natural products, synthetic products, crystalline, non-crystalline, hydrophobic, and hydrophilic silica. Silica can be synthesized by dry or wet methods, and the dry methods include combustion and arc methods, and the wet methods include precipitation and gel methods. Silica can be synthesized by any method. Silica can be hydrophilic silica having hydrophilic functional groups on the surface, or hydrophobic silica in which the hydrophilic functional groups are modified with alkylsilane or the like to be hydrophobic. Hydrophilic silica is preferred. Examples of such silica include the Nipgel series and Nipsil series manufactured by Tosoh Silica Corporation, and the Mizukasil series manufactured by Mizusawa Chemical Industry Co., Ltd.
[0037] (Kaolin) Kaolin may be produced by any of the following methods: wet kaolin, dry kaolin, and calcined kaolin. Examples of such kaolin include NN kaolin clay and kaolin clay 5M manufactured by Takehara Chemical Industry.
[0038] <Coloring pigments> As coloring pigments, organic pigments such as monoazo pigments, disazo pigments, phthalocyanine blue, phthalocyanine green, dioxazine violet, and diketopyrrolopyrrole, and inorganic pigments (excluding extender pigments) such as titanium oxide and carbon black can be used.
[0039] From the viewpoint of color development and drying properties, the solids ratio of the color pigment to barium sulfate in the water-based flexographic ink of the present invention is preferably 99:1 to 30:70, more preferably 90:10 to 40:50, and even more preferably 80:20 to 50:50.
[0040] <Additives> It is preferable to use various additives in the water-based flexographic ink of the present invention as necessary, such as a wetting agent, a dispersant, a wax, a defoaming agent, an organic amine, and a preservative. Specifically, there are dispersants for improving the dispersibility of inorganic pigments and color pigments, and among them, it is preferable to use a hydrocarbon wax such as polyethylene wax in order to improve the abrasion resistance. It is also preferable to use an organic amine in order to improve the cleaning properties. In addition, it is also preferable to use various additives such as a defoaming agent to impart defoaming properties and a preservative to prevent the putrefaction of the water-based flexographic ink.
[0041] (Hydrocarbon wax) Examples of the hydrocarbon wax include, but are not limited to, polyethylene wax, Fischer-Tropsch wax, paraffin wax, microcrystalline wax, polypropylene wax, etc. Among these, polyethylene wax and / or Fischer-Tropsch wax are preferred.
[0042] The hardness (penetration) of the hydrocarbon wax at 25°C as specified by JISK2207 is preferably 12 or less, more preferably 0.5 to 8, more preferably 1 to 5, even more preferably 2 to 4, and particularly preferably 2.5 to 3.5. When it is within the above range, the friction resistance is good. The density of the hydrocarbon wax at 23°C as specified by JISK7112 (Method B) is 900 to 990 kg / m 3 It is preferable that the viscosity is 925 to 990 kg / m 3 It is more preferable that the melting point is within the above range. When it is within the above range, the friction resistance is good. The melting point of the hydrocarbon wax in DSC measurement is preferably 90 to 150°C, and more preferably 100 to 125°C. When it is within the above range, the friction resistance is good. The melting point of the hydrocarbon wax refers to the melting point of the peak top (minimum value) of the endothermic peak in the DSC temperature rise curve. The average particle size of the hydrocarbon wax is preferably 0.5 to 12 μm, more preferably 1 to 10 μm, and even more preferably 1.5 to 4 μm. The average particle size of the hydrocarbon wax refers to the D50 value measured by dynamic light scattering.
[0043] The content of the hydrocarbon wax solids in the water-based flexo ink is preferably 0.1 to 10 mass %, more preferably 0.3 to 5 mass %, and even more preferably 0.5 to 3 mass %, based on 100 mass % of the water-based flexo ink.
[0044] <Aqueous medium> The aqueous flexographic ink contains an aqueous medium. The main component of the aqueous medium (50% by mass or more of the total mass of the entire aqueous medium) is preferably water, but the aqueous medium can contain a hydrophilic organic solvent in addition to the main component water. Specifically, the hydrophilic organic solvent preferably contains an alcohol-based organic solvent and / or a glycol-based organic solvent depending on the printing conditions (speed, plate depth, design, drying temperature). It is more preferable to contain an alcohol-based organic solvent. The hydrophilic organic solvent is preferably contained in an amount of 10 to 20% by mass, more preferably 5 to 10% by mass, of the total mass of the aqueous medium. In the present invention, the water-soluble organic solvent refers to a solvent that is liquid at 25° C. and has a solubility in water at 25° C. of 1% by mass or more.
[0045] Examples of the alcohol-based organic solvent include methanol, ethanol, propanol, isopropanol, isobutanol, normal butanol, tertiary butanol, hexanol, octanol, and decanol.
[0046] Examples of the glycol-based organic solvent include acetylene diol, ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monooctyl ether, diethylene glycol, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, triethylene glycol, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monopropyl ether, triethylene glycol monobutyl ether, propylene glycol, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol, tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, tripropylene glycol monopropyl ether, tripropylene glycol monobutyl ether, and dibutyl glycol. These may be used alone or in combination of two or more.
[0047] <How water-based flexographic ink is manufactured> Water-based flexographic ink can be produced by dispersing pigments and resins in an organic solvent using a disperser or the like, and further mixing the resulting pigment dispersion with resins, various additives, organic solvents, and the like as necessary. As the disperser, a commonly used one, such as a roller mill, a ball mill, a pebble mill, an attritor, or a sand mill, can be used. The particle size distribution of the pigment in the pigment dispersion can be adjusted by appropriately adjusting the size of the grinding media of the disperser, the filling rate of the grinding media, the dispersion processing time, the discharge speed of the pigment dispersion, the viscosity of the pigment dispersion, and the like. The viscosity of the printing ink at 25°C is preferably in the range of 50 mPa·s or more from the viewpoint of preventing the pigment from settling and dispersing appropriately, and 300 mPa·s or less from the viewpoint of workability efficiency during ink production and printing. For example, the method described in JP-A-2018-158986 can be used as the method for producing the printing ink.
[0048] (Viscosity of water-based flexographic ink) The viscosity of the aqueous flexographic ink produced by the above method is preferably in the range of 40 to 700 cps at 25°C as measured by a Brookfield viscometer in order to accommodate high-speed printing (50 to 400 m / min) in flexographic printing. More preferably, it is in the range of 50 to 500 cps. This viscosity range corresponds to a viscosity of about 9 to 40 seconds as measured by Zahn cup #4. The viscosity of the aqueous flexographic ink can be adjusted by appropriately selecting the types and amounts of the raw materials used, for example, the amounts of the acrylic resin emulsion, the extender pigment, the styrene-maleic acid resin, and the aqueous medium.
[0049] [Printed material] The aqueous flexographic ink of the present invention can be used for printing by known printing methods. Among them, flexographic printing is preferred. For example, the aqueous flexographic ink is diluted with an aqueous medium to a viscosity and concentration suitable for flexographic printing, and supplied to each printing unit alone or in a mixture. After printing on a substrate using the aqueous flexographic ink of the present invention, a printed layer is formed by removing volatile components, and a printed matter can be obtained.
[0050] <Base material> The substrate is not particularly limited, and known substrates can be used, and a paper substrate is preferable. For example, K-liner, nonwoven fabric, medium-quality paper, wood-free paper, newsprint, Yupo paper, various coated papers, lining paper, impregnated paper, cardboard, art paper, cast paper, one-sided glossy kraft paper, bleached kraft paper, unbleached kraft paper, coated board, ivory paper, card paper, cup base paper, cast paper, light-shielding paper, and surface-treated paper substrates thereof can be mentioned, and a K-liner is more preferable. In addition, a vapor-deposited paper substrate in which an inorganic compound such as silica, alumina, or aluminum is vapor-deposited on a paper substrate can also be used, and an anchor layer may be used to uniformly form a vapor-deposited layer on the paper substrate, and the vapor-deposited layer may further be coated with polyvinyl alcohol or the like. Furthermore, a paper substrate in which a heat-sealable resin such as polyethylene is formed on the vapor-deposited layer can also be used. In addition, various melamine papers in which the above-mentioned paper substrates are impregnated with melamine resin can be used. In addition, the paper substrate can be 50 to 150 g / m 2 It is preferable that the thickness is 60 to 120 g / m 2 More preferably, the thickness is 60 to 90 g / m 2 It is more preferable that:
[0051] <Flexographic printing method> Flexographic printing methods include the two-roll method, doctor method, and doctor chamber method. In any of the two-roll method, doctor method, and doctor chamber method, the aqueous flexographic ink is supplied to an anilox roll having cells formed on its surface, and the excess aqueous flexographic ink on the anilox roll surface is scraped off with a roll or doctor blade, and the ink is finally printed on a substrate through a resin plate. When the aqueous flexographic ink of the present invention is printed by the flexographic printing method, a printed matter having excellent aesthetic appearance can be obtained even on a paper substrate having a rough surface. EXAMPLES
[0052] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the present invention, parts and % represent parts by mass and % by mass unless otherwise noted. In addition, "solid content" represents the total mass % of non-volatile content.
[0053] <<Measurement of hydroxyl value>> In the present application, the hydroxyl value is the number of milligrams of potassium hydroxide required to acetylate the hydroxyl groups contained in 1 g of resin solid content and neutralize the acetic acid bonded to the hydroxyl groups, and is measured in accordance with JIS K 0070.
[0054] <Acid value measurement> In the present invention, the acid value is the number of milligrams of potassium hydroxide required to neutralize the acidic groups contained in 1 g of resin solid content, and is measured in accordance with JIS K 0070.
[0055] <<Measurement of glass transition temperature>> In the present invention, the glass transition temperature was measured by simultaneous thermogravimetry and differential thermal analysis (TG-DTA) using a DTG-60A manufactured by Shimadzu Corporation. In detail, the glass transition temperature was determined as the inflection point temperature in the baseline shift under the conditions of a nitrogen atmosphere, a measurement temperature range of −100 to 200° C., and a heating rate of 1° C. / min.
[0056] <Measurement of weight average molecular weight> In the present invention, the weight average molecular weight can be determined as a converted molecular weight using polyethylene glycol as a standard substance, and the measuring device used was a GPC device: Shodex GPC-401 manufactured by Showa Denko K.K. The column was a Shodex OHpak LB-805 manufactured by Showa Denko K.K., and the detector was an RI (differential refractometer). The eluent used was a 0.1N NaNO3 aqueous solution, and the column temperature was 35°C, and the flow rate was 3 mL / min.
[0057] <Measuring average particle size> In the present invention, the average particle size can be measured by a dynamic light scattering method, and the measurement is performed in water using a particle size distribution measuring device: MT3300EX II manufactured by Microtrac MRB in accordance with JIS Z8825-2013.
[0058] <Synthesis Example 1> Synthesis of urethane resin solution PU1 In a reactor equipped with a thermometer, a stirrer, a reflux condenser and a nitrogen gas inlet tube, 173.7 parts of poly(3-methyl-1,5-pentane adipate)diol (number average molecular weight 2000), 9.1 parts of polyethylene glycol (number average molecular weight 2000), 21.5 parts of 2,2-dimethylolpropionic acid and 84 parts of isophorone diisocyanate were charged with 200 parts of methyl ethyl ketone while introducing nitrogen gas, and the mixture was heated and refluxed for 6 hours while stirring. After cooling to 40°C, 100 parts of acetone were added to obtain a solution of terminal isocyanate prepolymer. Next, the obtained terminal isocyanate prepolymer solution was gradually added at room temperature to a mixture of 8.7 parts of 2-hydroxyethylethylenediamine, 2.9 parts of isophoronediamine and 400 parts of acetone, and reacted at 50°C for 3 hours to obtain a solvent-based urethane resin solution. Next, 9.8 parts of 28% by mass ammonia water and 700 parts of deionized water were gradually added to the above solvent-based urethane resin solution to neutralize and make it water-soluble, and then all of the methyl ethyl ketone and acetone were distilled off under azeotropic conditions, and water was added to adjust the viscosity, obtaining urethane resin PU1 with an acid value of 30 mgKOH / g, a solids content of 40% by mass, and a weight average molecular weight of 30,000.
[0059] Example 1: Preparation of water-based flexographic ink V1 A mixture of 21.3 parts of water, 3.5 parts of water-soluble acrylic resin 1 (acid value 213 mg KOH / g, weight average molecular weight: 8000, glass transition temperature: 73 ° C, neutralizer: ammonia, solid content 30%), 6 parts of barium sulfate A1 (product name: Variace B35, Sakai Chemical Industry Co., Ltd., particle size: 0.3 μm), 18 parts of color pigment (Ramdev Chemical Industries Co., Ltd., phthalocyanine blue, product name: Ramafast Blue WP / L-143), 0.8 parts of Brownon P178 (Aoki Oil Industry Co., Ltd., dispersant, polyoxyethylene polyoxypropylene glycol copolymer, solid content 100%), and 0.2 parts of acetylene diol was kneaded and dispersed in a bead mill, and then 23 parts of acrylic resin emulsion AC1 (acid value 22 mg KOH / g, glass transition temperature: 87 ° C, neutralizer: ammonia, solid content .50%), styrene malic acid ester 100% was added. The following were added and mixed so as to obtain water-based flexographic ink V1: 1.5 parts of acrylic acid resin SM1 (acid value 195 mg KOH / g, weight average molecular weight: 2600, degree of alkyl esterification 50 mol%, neutralizer: ammonia, solid content .37%), 21 parts of water-soluble acrylic resin 2 (acid value 280 mg KOH / g, weight average molecular weight: 6500, glass transition temperature: 128 ° C., neutralizer: ammonia, solid content .32%), 1.5 parts of Newcol 780-60 (manufactured by Nippon Nyukazai Co., Ltd., nonionic surfactant, polycyclic phenyl copolymer, solid content 60%), 0.2 parts of preservative (1,2-benzisothiazolin-3-one, solid content 20%), 1.5 parts of polyethylene wax (solid content 40%), 0.6 parts of silicone antifoaming agent (solid content 25 mass%), 0.6 parts of triethanolamine, and 0.3 parts of monoethanolamine.
[0060] In addition, Brownon P178, acetylene diol, Newcol 780-60, preservatives, polyethylene wax, silicone antifoaming agent, triethanolamine, and monoethanolamine are listed collectively in Table 1 as "additives 5.7 parts."
[0061] <Examples 2 to 21 and Comparative Examples 1 to 5> Preparation of Water-Based Flexographic Inks V2 to 26 Water-based flexographic inks V2 to 26 were obtained in the same manner as in Example 1, except that the raw materials and blending ratios shown in Tables 1 and 2 were used. The properties of the raw materials used are as follows. Acrylic resin emulsion AC2 (acid value 22 mgKOH / g, glass transition temperature: 20°C, neutralizer: ammonia, solid content: 50%) Acrylic resin emulsion AC3 (acid value 22 mg KOH / g, glass transition temperature: 120°C, neutralizer: ammonia, solid content 50%) Styrene-maleic acid resin SM2 (acid value 195 mg KOH / g, weight average molecular weight: 30,000, alkyl esterification degree 50 mol%, neutralizer: ammonia, solid content 37%) Styrene-maleic acid resin SM3 (acid value 195 mg KOH / g, weight average molecular weight: 60,000, alkyl esterification degree 50 mol%, neutralizer: ammonia, solid content 37%) Styrene-maleic acid resin SM4 (acid value 195 mg KOH / g, weight average molecular weight: 120,000, alkyl esterification degree 50 mol%, neutralizer: ammonia, solid content 37%) Styrene-maleic acid resin SM5 (acid value 195 mg KOH / g, weight average molecular weight: 100, alkyl esterification degree 50 mol%, neutralizer: ammonia, solid content 37%) Styrene-maleic acid resin SM6 (acid value 195 mg KOH / g, weight average molecular weight: 2600, alkyl esterification degree 20% (molar), neutralizer: ammonia, solid content 37%) Styrene-maleic acid resin SM7 (acid value 195 mg KOH / g, weight average molecular weight: 2600, alkyl esterification degree 70% by mole, neutralizer: ammonia, solid content 37%) Styrene-maleic acid resin SM8 (acid value 195 mg KOH / g, weight average molecular weight: 2600, alkyl esterification degree 0 mol%, neutralizer: ammonia, solid content 37%) Styrene-maleic acid resin SM9 (acid value 195 mg KOH / g, weight average molecular weight: 2600, alkyl esterification degree 90 mol%, neutralizer: ammonia, solid content 37%) Extender pigment: calcium carbonate (average particle size 1μm, oil absorption 40ml / 100g) · Extender pigment: Silica (average particle size 4μm, oil absorption 200ml / 100g)
[0062] [Table 1]
[0063] [Table 2]
[0064] [Evaluation of water-based flexographic ink] The obtained water-based flexographic inks V1 to 26 were evaluated as described below. The evaluation results are shown in Tables 1 and 2.
[0065] <Drying> Water-based flexographic ink was applied to a PET film using a Meyer bar (K control coater) #6, and the surface coated with water-based anti-slip varnish was touched with a finger every 10 seconds to measure the time until the tack was lost and evaluated according to the following criteria. "Tack" refers to the presence of adhesion. A, B, and C are ranges that do not pose any practical problems. Evaluation Criteria A: The time it takes for the tack to break is less than 20 seconds. B: The time it takes for the tack to break is between 20 and 30 seconds. C: Time until the tack breaks is between 30 and 40 seconds D: Time until the tack breaks is more than 40 seconds
[0066] <Cleaning ability> Water-based flexographic ink was applied to a resin plate using a Meyer bar (K control coater) #4, and after 10, 20, and 30 minutes, the ink was wiped off with absorbent cotton soaked in water, and the degree of dissolution of the coating was visually evaluated. A, B, and C are ranges that are acceptable for practical use. Evaluation Criteria A: Even at 30 minutes, the coating had dissolved. B: The coating film dissolved at 20 minutes, but did not dissolve at 30 minutes. C: The coating film dissolved at 10 minutes, but did not dissolve at 20 minutes. D: When wiped off after 10 minutes, the coating did not dissolve.
[0067] <Metastatic> Water-based flexographic ink was printed on the water-repellent paper at a printing speed of 50 m / min using a small Flexiproof printing machine (flexographic printing machine) equipped with a 250 line / inch anilox roll and a solid plate made of photosensitive resin, and transferability was evaluated according to the following criteria. Note that the transferability test to water-repellent paper was conducted under extreme conditions, since the water repellency is extremely high due to the water repellent agent applied to the substrate surface. Evaluation Criteria A. Transfer rate to water-repellent paper is 100% by mass B. The transfer rate to water-repellent paper is 75% by mass or more but less than 100% by mass. C. Transfer rate to water-repellent paper is 50% by mass or more but less than 75% by mass D. The transfer rate to water-repellent paper is less than 50% by mass.
[0068] <Abrasion resistance> K-liner (craft paper base material, basis weight: 250g / m 2 ) was coated with water-based flexographic ink using a Meyer bar (K control coater) #4, and dried at room temperature for 24 hours to create a print, which was then cut into two pieces measuring 40 mm square, and one piece measuring 25 mm x 150 mm. The rub resistance was evaluated according to the following criteria using a Gakushin-type rub fastness tester manufactured by Tester Sangyo Co., Ltd. A, B, and C are ranges that are acceptable for practical use. Test conditions Load: 500g, Number of reciprocations: 100, Paper: High-quality paper Evaluation Criteria A. The amount of ink adhering to the paper is less than 10% by weight. B. Ink adhesion to the paper is between 10% and 30% by weight C. Ink adhesion to the paper is 30% to less than 50% by weight D. The amount of ink adhering to the paper is 50% or more by weight.
[0069] <Stability over time> 100 g of water-based flexographic ink was placed in a plastic bottle and left to stand at 40°C for one week, and the stability over time was evaluated according to the following criteria. A. Thickening in less than 5 seconds using Zahn cup #4 B. Thickening for 5 to 10 seconds using Zahn cup #4 C. Thickening for 10 to 20 seconds using Zahn cup #4 D. Thickening for 20 seconds or more using Zahn cup #4
[0070] From the above results, Comparative Example 1 did not contain an acrylic resin emulsion, and therefore had poor cleaning properties, transfer properties, abrasion resistance, and stability over time. Comparative Examples 2, 4, and 5 did not contain barium sulfate, and therefore had poor drying properties and transfer properties. Comparative Example 3 did not contain a styrene-maleic acid resin, and therefore had poor transfer properties. On the other hand, since the examples contained an acrylic resin emulsion, barium sulfate, and a styrene-maleic acid resin, they were excellent in drying properties, washability, transferability, abrasion resistance, and stability over time. In particular, Example 1, which had an acrylic resin emulsion with a glass transition temperature of 87°C, a styrene-maleic acid resin with a weight average molecular weight of 2600, a degree of alkyl esterification of 50 mass%, contained a water-soluble acrylic resin and a coloring pigment, had a solids mass ratio of barium sulfate to styrene-maleic acid resin of 92 / 57, a solids mass ratio of the coloring pigment to barium sulfate of 75 / 25, a solids ratio of the acrylic resin emulsion to the water-soluble acrylic resin of 65 / 35, and contained polyethylene wax, had excellent drying properties, washability, transferability, abrasion resistance, and stability over time.
Claims
1. A water-based flexographic ink containing an acrylic resin emulsion, barium sulfate, and a styrene-maleic acid resin.
2. 2. The water-based flexographic ink according to claim 1, wherein the average particle size of the barium sulfate is 0.1 to 2 μm.
3. 3. The water-based flexographic ink according to claim 1, wherein the oil absorption of the barium sulfate is 10 to 100 ml / 100 g.
4. 3. The water-based flexographic ink according to claim 1, further comprising a color pigment.
5. 5. The water-based flexographic ink according to claim 4, wherein the solids mass ratio of the color pigment to the barium sulfate is 99:1 to 30:
70.
6. 3. The water-based flexographic ink according to claim 1, wherein the solid content mass ratio of barium sulfate to styrene-maleic acid resin is 99:1 to 30:
70.
7. 3. The water-based flexographic ink according to claim 1, wherein the styrene-maleic acid resin has an alkyl ester structure.
8. The water-based flexographic ink according to claim 1 or 2, further comprising a water-soluble acrylic resin.
9. A printed matter having a printing layer comprising the water-based flexographic ink according to claim 1 or 2 on a substrate.
Citation Information
Patent Citations
Aqueous printing ink
JP1979074104A
Printing ink
JP1980012192A
Production of resin binder for water-based flexographic ink
JP1987179504A
Aqueous printing ink composition
JP1988227674A
Aqueous printing ink composition
JP1997217034A
Cited By
Method for producing light-transmitting packaging material and clearing agent solution
JP7938760B1